Maturation of Speech and Language Functional Neuroanatomy in Pediatric Normal Controls. - Devous, Michael D.; Altuna, Dianne; Furl, Nicholas (Journal of Speech, Language & Hearing Research, 2006)
Purpose: This study explores the relationship between age and resting-state regional cerebral blood flow (rCBF) in regions associated with higher order language skills using a population of normal children, adolescents, and young adults. Method: rCBF was measured in 33 normal participants between the ages of 7 and 19 years using single photon emission computed tomography. Participants' ages were regressed on rCBF values (normalized to whole-brain CBF) in 2 ways: (a) within anatomically defined, language-related regions of interest (ROIs) including Wernicke's area, Broca's area, angular gyrus, planum temporale, and Heschl's gyrus and (b) within clusters of voxels found to be significantly related to age in voxel-wise analyses. Results: rCBF in all anatomically defined ROIs except Heschl's gyrus declined as a function of age. Additionally, voxel-wise analyses revealed clusters where rCBF declined with age in left inferior parietal, left superior temporal, and right middle temporal regions—areas often implicated in higher order language functions. Conclusions: These data suggest that ongoing maturation (e.g., dendritic pruning) in higher order cognitive areas (e.g., angular gyrus) continues into adolescence, as reflected by declining rCBF, while the primary auditory area (Heschl's gyrus) has become a stable neuronal population by age 7 years. Reprinted by permission of the publisher.